IMPROVING ACADEMIC COMPETENCE THROUGH PROFESSIONAL HUMAN RESOURCE DEVELOPMENT: A CASE STUDY OF MUHAMMADIYAH UNIVERSITY OF TANGERANG AND SYEKH YUSUF ISLAMIC UNIVERSITY - Sukanti, Lina; Sutarman, Sutarman (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
This study examines the role of professional human resource development in improving academic competence at Muhammadiyah University of Tangerang and Syekh Yusuf Islamic University. Background: Academic competence is a critical factor in enhancing the quality of higher education, particularly in teaching, research, and community service. Purpose: This research aims to analyze human resource development strategies, including training programs, professional certification, performance evaluation, and career development, and their contribution to strengthening academic competence in both institutions. Method: Using a qualitative case study approach, data were collected through document analysis, in-depth interviews, and observations involving academic leaders, lecturers, and human resource management units. Result: The findings reveal that systematic and continuous human resource development significantly enhances lecturers’ pedagogical skills, research capacity, and professional commitment. Furthermore, institutional support and alignment between human resource policies and academic goals play an important role in sustaining academic competence. Conclusion: This study concludes that professional human resource development is a key driver in improving academic competence and institutional performance in higher education, and it provides practical insights for universities seeking to strengthen their human capital strategies.